Early CT Findings of Global Central Nervous System Hypoperfusion - Kjos, Bent O.; Brant-Zawadzki, Michael; Young, Robyn G. (American Journal of Neuroradiology, 1983)
The early computed tomographic (CT) findings of acute global central nervous system hypoperfusion were studied in 10 patients. The findings could be characterized as: (1) diffuse mass effect with effacement of the cerebral sulci and of the brainstem cisterns (nine patients); (2) global decrease in the cortical gray-matter density from edema, causing loss of the normal gray-white matter differentiation (six patients); (3) low-density lesions of the basal ganglia bilaterally (five patients); and (4) decreased gray-matter density in watershed distributions bilaterally (two patients). Subsequent contrast-enhanced scans in three of the 10 patients demonstrated selective enhancement of the cerebral cortex or the basal ganglia or both. The CT findings seen in this study predicted a poor outcome; nine of the 10 patients died from the insult. The abnormal CT findings can be ascribed to increased vulnerability of the cerebral cortex and basal ganglia to hypotensive episodes. This vulnerability is due to the large metabolic demand of these regions and their characteristic local cerebral blood flow.